Equity valuation Asos PLC - Marques, Mariana Borges (2015)
This thesis aims to study the value of Asos PLC. The valuation was based in four methodologies, the Discounted Cash Flow (DCF), the Economic Value Added (EVA), the Trading Multiples and the Transaction Multiples. Using the DCF method, a price of 3.054p was obtained and the EVA yielded a comparable lower value of 2.528p. Regarding the Relative Valuation, this was the method which delivered the lowest values of 1.573p for the Trading Multiples and 1.253p for the Transaction Multiples. It was concluded that the four methodologies yielded different prices per share, though the DCF being the most accurate and complete model to demonstrate Asos’ intrinsic value. Given this and comparing the DCF output to the market valuation, Asos’ stock was rated as being Overweight. Nonetheless, a sensitivity analysis was conducted in order to test how the valuation could change, along with the variation of some of the model’s sources of uncertainty. The conclusion of this analysis was that, changes in both WACC and perpetual growth rate variables, would significantly affect the outcome of the valuation, although the WACC being responsible for greater impacts. Additionally, a more in-depth analysis to Asos’ stock price performance from 2001 to 2014 was conducted. When applying the Value at Risk statistical technique, it was concluded that, with 99% confidence level, an investor is exposed to the risk of losing 8,90% of the total amount invested in Asos. Finally, this thesis’ valuation was compared to the most recent J. P. Morgan report about this equity. Both final recommendations were DCF-based and some fundamental inputs were estimated very closely, such as the WACC and the perpetual growth rate. The report presented a final recommendation of Overweight, with a price target of 3.100p, being very approximate to the result of this study of 3.054p.